The effect of brand trust, brand satisfaction and customer value on consumers’ brand loyalty: in the context of Azerbaijan and foreign brands - Kamilov, Hikmat (Annals of Spiru Haret University. Economic Series, 2021)
Businesses that determine the areas that customers are not satisfied with or that want to make their satisfied customers more satisfied are making a great effort for this. It is not possible for businesses to establish good relations with customers they cannot satisfy and to gain their loyalty. Accordingly, learning what customers want and fulfilling these requests in the best way has become an issue that businesses need to focus on. The aim of the research is to examine the effect of customer satisfaction on marketing in the service sector. In this direction, it was aimed to determine the dimensions of customer satisfaction and to examine the relationships between these dimensions. At the same time, it has been analyzed in detail how the dimensions of customer satisfaction differ according to the characteristics of the customers, which customer characteristics and to what extent the customer satisfaction dimensions are affected.